Twin deficits hypothesis in SEACEN countries: a panel data analysis of relationships between public budget and current account deficits - Evan, Lau; Ahmad Zubaidi, Baharumshah (Euro-American Association of Economic Development, 2006)
In this paper, the twin deficits hypothesis was examined using the panel data of nine SEACEN countries. Empirical results provide evidence to support the view that Asian budget deficit causes current account deficit directly as well as indirectly. From policy perspectives, the statistical analysis suggests that managing budget deficit offers scope for improvement in the current account deficit. However, this finding does not support the policy of manipulating the intermediate variables to reduce the twin deficits to a sustainable level since these variables appear to be endogenous in the system.